Evolution of staff motivation management tools in digital reality - O. K. Mineva; E. V. Polyanskaya (Новые технологии, 2021)
Traditional motivation tools are almost completely focused on meeting the basic needs of a person. Until 2010 the management science did not consider the satisfaction of the highest needs of a person as a priority, however, the satisfaction of a person’s basic needs in the 21st century is considered as a presume, and the toolkit that formed it significantly limits the efficiency of companies. A feature of a modern employee is his high level of education, formed digital skills, deep socialization, which manifests itself in a request to an employer about working conditions that allow finding an acceptable balance between work and personal life, the constant development of competencies and a consistent change in status. At the same time, the portrait of a modern employer has also changed, and now the effectiveness of an employee is important with the maximum possible cost optimization. This requires a significant change in the mentality of HR workers, employers and their search for new motivation tools. The 2020 lockdown has significantly transformed the scale of employee values and require employers to promptly modify the usual business models. The result of the lockdown is a large case of motivation tools, for which there were requests even before the COVID pandemic. Scientists have received a one-time approbation of new motivation tools around the world. Within the framework of the research, we have carried out work on the systematization of the most effective motivation tools and their application in accordance with the highest needs of the individual. The introduction of modern motivation tools into the practice of companies can significantly increase the attractiveness of work in it for employees, achieve an increase in labor efficiency while reducing conditionally fixed costs.